The Impact of Sharia-Based Green Investment on Community Welfare and Environmental Sustainability in Indonesia - Sugianto Sugianto; Andriani Puspitaningsih; Musennif Zeynaddin Shabanov (Green Economics: International Journal of Islamic and Economic Education, 2024)
Environmental degradation and poverty remain pressing challenges in Indonesia, exacerbated by rapid economic growth and resource exploitation. The increasing demand for sustainable development has highlighted the need for alternative financial models that integrate both economic growth and environmental protection. Sharia-based green investments have emerged as a promising solution, offering a framework that aligns ethical considerations with sustainability goals. This study examines the impact of Sharia-based green investments on social welfare and environmental sustainability in Indonesia, with a focus on reducing income inequality and fostering community development. Using a mixed-method approach, including quantitative analysis of secondary data on green investment performance and qualitative interviews with key stakeholders, the research evaluates how these investments contribute to enhancing income equality, providing access to renewable energy, and promoting sustainable economic activities. Findings show that Sharia-based green investments not only improve income distribution, especially in rural areas and small businesses, but also contribute to environmental sustainability through renewable energy projects and eco-friendly infrastructure. The study also compares the environmental benefits of Sharia-based investments with conventional models, emphasizing their superior alignment with long-term sustainability goals. The research underscores the potential of Sharia-based green investments as a model for inclusive economic growth and environmental protection, supporting Indonesia’s progress toward achieving the Sustainable Development Goals (SDGs).